Cloning and identification of a novel virulence gene of Xanthomonas campestris pv. campestris - LU Guang-tao; TANG Ji-liang; HE Yong-qiang; CHEN Bao-shan; WEI Guang-ning (浙江大学学报. 农业与生命科学版)
Xanthomonas campestris pv. campestris (Xcc) is the pathogenic agent of black rot disease in cruciferous plants. The wild-type strain 8004 of Xcc was mutagenized with transposon Tn5gusA5, and 17280 strain of Tn5gusA5 mutants were obtained. From these Tn5gusA5 mutants, a number of virulence-deficient mutants were isolated. The insertion sites of these virulence-deficient mutants were analyzed using TAIL-PCR, and the corresponding genes were identified by homology blast to the completely sequenced genome of Xcc 8004 strain (data not published). A novel gene, wbxL, identified from 5 strains of virulence-deficient mutants, was found to be disrupted by the insertion of Tn5gusA5 in ORF1857 of the genome. This gene showed 33% identity and 45% similarity to the wbpL gene of Pseudomonase aeruginosa at amino acid level, with characteristics of glycostransferase 4th family domain. wbxL gene was deleted and the virulence of the deletion mutant disappeared completely following innoculation into radish by clipping. The deletion mutant could be complemented in trans with a PCR fragment containing an intact wbxL gene so that the virulence of the mutant was restored. The data confirmed the involvement of wbxL gene in the virulence of Xcc.